2003
DOI: 10.1034/j.1399-3038.2003.00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Correction of bronchial challenge data for age and size may affect the results of genetic association studies in children

Abstract: Meaningful studies of asthma genetics require careful definition of airway hyperresponsiveness (AHR). In children, several studies have emphasized the need for correction of bronchial challenge data for baseline parameters, such as age, gender, lung function and atopic status, when undertaking airway responsiveness measurements. However, few studies have suggested how this should be performed in practice. This study describes a method for the correction of dose-response slopes (DRS) and PC20 values for baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In a population of asthmatic families from North Staffordshire we have demonstrated a protective effect of child and maternal GSTP1 Val 105 /Val 105 genotype on measures of corrected AHR (17). Paternal GSTP1 Val 105 /Val 105 genotype did not influence offspring corrected AHR, and the effects of maternal GSTP1 genotype appeared independent of transmission to the offspring.…”
Section: Candidate Maternal Genesmentioning
confidence: 89%
See 2 more Smart Citations
“…In a population of asthmatic families from North Staffordshire we have demonstrated a protective effect of child and maternal GSTP1 Val 105 /Val 105 genotype on measures of corrected AHR (17). Paternal GSTP1 Val 105 /Val 105 genotype did not influence offspring corrected AHR, and the effects of maternal GSTP1 genotype appeared independent of transmission to the offspring.…”
Section: Candidate Maternal Genesmentioning
confidence: 89%
“…This genotype has been shown to protect against the asthma phenotypes of airway hyperresponsiveness (AHR) and atopy in adults (13, 14). Moreover, variations in GSTP1 also appear to influence susceptibility to childhood respiratory illness (15; Val 105 /Val 105 being protective), childhood lung function growth (16), atopic status and corrected AHR (17). A further polymorphism is present at codon 114 in exon 6.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, this has been confirmed by Anyacioglu et al [8], who showed a threefold lower risk of asthma in Val 105 homozygotes compared with the wild‐type genotype in a Turkish adult population. Other studies had also confirmed the protective effect of GSTP1 Val 105 homozygosity on asthma phenotypes: in Italian patients with occupational asthma [9], in children with asthma from Taiwan [10], UK [11] and Tunisia [12]. Furthermore, this genotype has been linked to improved lung function in children [14] and in Japanese patients with COPD [15].…”
mentioning
confidence: 83%
“…The GSTs are a supergene family of enzymes that are essential to the detoxication of these products of oxidative stress. There is increasing evidence that asthma is associated with increased oxidative stress [6] and that polymorphism in GSTs may influence susceptibility to asthma, atopy and airway hyperresponsiveness (AHR) [7][8][9][10][11][12].…”
mentioning
confidence: 99%